Kajian Partisipasi Masyarakat dalam Operasional dan Pemeliharaan Jaringan Irigasi Blang Ara Keude - idris, fadli idris; Febrianti, Dian -; Amir, Astiah -; Satria, Andrisman -; Alvisyahri, Alvisyahri - (Universitas Teuku Umar, 2025)
As an agricultural country, Indonesia heavily depends on the agricultural sector to support its national economy, with the majority of its population relying on agriculture for their livelihood. The development and maintenance of irrigation infrastructure are vital for meeting food demands and enhancing agricultural productivity. This study aims to examine community participation in the operation and maintenance of irrigation networks in Gampong Blang Ara Keude, Seunagan Timur District Nagan Raya Regency. A mixed-method approach was employed, utilizing both qualitative and quantitative data collected through surveys and questionnaires administered to 62 respondents, including farmers, agricultural laborers, village officials, and irrigation supervisors (keujruen blang). Secondary data were sourced from demographic statistics and location maps. The findings indicate that many irrigation networks in the area require regular maintenance. Levels of community participation vary, but most contributions are observed in the form of physical labor, material support, and idea sharing. Validity and reliability tests, conducted using Pearson’s correlation and Cronbach’s Alpha, confirmed the instruments' reliability and consistency. Analysis through dichotomous and Likert scales demonstrates that the sustainability of irrigation systems is strongly influenced by active community involvement and effective government oversight. The primary challenges identified include insufficient resources and limited access to modern irrigation technologies. The study concludes that strengthening community participation, alongside consistent governmental support, can significantly improve irrigation performance, increase agricultural yields, and reinforce local food security. Recommendations include more frequent maintenance efforts, enhanced community education, and improved resource allocation to ensure the long-term sustainability of irrigation systems.